Decolonizing research and critical thinking training in social sciences - BARONNET, Bruno (Utopía y Praxis Latinoamericana, 2022)
This paper addresses the significance and the challenges of various decolonized practices in research and in social science training methods in Mexico and, particularly, in Chiapas, based on a Latin American approach to the field of studies conducted by intellectuals and activists involved in social movement struggles. We analyze different forms of intercultural dialogues used in decolonizing research in terms of social, ethnic and gender relationships, according to the contexts and the knowledge production of popular and indigenous movements facing politics, education and epistemic racism.